Construction and development of simliki forest virus vectors for transient gene therapy of model tumours in mice - İskender, Güniz (Trinity College (Dublin, Ireland). Department of Microbiology, 2010)
Cancer is a molecular and genetic disease that results from multiple alterations of genes, including proto-oncogenes and tumour-suppressor genes. Virotherapy is a branch of cancer gene therapy where oncolytic viruses are used to treat cancerous cells. Semliki Forest virus (SFV) and its derived vectors (recombinant or replication- competent) have been utilised for the treatment of cancer by exploiting their inherent apoptosis-inducing ability or by expressing high amounts of therapeutic proteins.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin